The living Lincoln - Horrocks, Thomas A.; Holzer, Harold; Williams, Frank J. (Southern Illinois University Press, 2011)
The Living Lincoln gives new voice to several aspects of Abraham Lincoln's career as seen through the lens of recent scholarship, in essays that show how the sixteenth president's appeal continues to endure and expand. Featuring eleven essays from major historians, the book offers thoughtful, provocative, and highly original examinations of Lincoln's role as commander-in-chief, his use of the press to shape public opinion, his position as a politician and party leader, and the changing interpretations of his legacy as a result of cultural and social changes over the century a.